Methods for determining the solvency and liquidity of an enterprise - Shirinov, B.; Ahmedova, А.; Ahmedov, U.; Ширінов, Б.; Ахмедова, А.; Ахмедов, У. (Харківський національний автомобільно-дорожній університет, 2025)
The article is dedicated to the methods of assessing the solvency and liquidity of an enterprise, which are key aspects for ensuring its financial stability and competitiveness in the market. The study presents a comprehensive analysis of financial indicators, including the liquidity of assets and liabilities, using various financial analysis methods. The focus is placed on horizontal, vertical, and trend analysis, which allows for the assessment of changes in the financial position of the enterprise over several years. The article also includes an analysis of the balance sheet liquidity to qualitatively assess the solvency and liquidity of the enterprise, as well as to investigate the sources of its financial condition. The balance sheet of the production and commercial enterprise "Senan" for the years 2021-2023 is analyzed using horizontal and vertical methods. Changes in the structure of assets and liabilities are studied, particularly the value of long-term and current assets, as well as their impact on the liquidity of the enterprise. To assess liquidity, key liquidity ratios were used, including the current, quick, and absolute ratios, which help determine the company's ability to meet its short-term obligations. According to the calculations, the company has sufficient liquidity to cover current debts in critical situations. The results of the study show that the enterprise has adequate liquidity to meet its current debts when necessary. The article also proposes a series of practical recommendations to improve the financial stability of the company, including strengthening control over accounts receivable, creating a reserve for doubtful debts, and implementing short-term financial investments. These measures are identified as enabling the reduction of debt, freeing up additional funds, and increasing working capital, which contributes to improving operational efficiency in a changing economic environment. The developed recommendations are of significant importance for ensuring the long-term financial stability of the enterprise.
Методи визначення платоспроможності та ліквідності підприємства
Keywords: liquidity; balance sheet; accounts receivable; financial stability; horizontal analysis; vertical analysis; absolute growth; relative growth; solvency; ліквідність; баланс; дебіторська заборгованість; фінансова стійкість; горизонтальний аналіз; вертикальний аналіз; абсолютне зростання; відносне зростання; платоспроможність; 330.657.631; 10.30977/ЕТК.2225-2304.2025.45.122